Prevalence of malaria and associated factors among symptomatic pregnant women attending antenatal care at three health centers in north-west Ethiopia - Almaw, Andargachew; Yimer, Mulat; Alemu, Megbaru; Tegegne, Banchamlak (PLOS ONE, 2022)
Background Malaria is the disease caused by Plasmodium species and primarily transmitted by the bite of female Anopheles mosquitoes. During pregnancy, malaria causes life threatening outcomes to the mother, the fetus and the new born. Even though, malaria symptomatic pregnant women highly attract mosquitoes and have higher potential of transmitting the disease in communities, most of the previous studies focused on pregnant women with asymptomatic Plasmodium infections. Therefore, the aim of this study was to assess the prevalence of malaria and associated factors among symptomatic pregnant women attending antenatal care at three health centers in northwest Ethiopia. Methods A health facility based cross-sectional study was conducted from February to April, 2021. A total of 312 malaria symptomatic pregnant women were involved from three health centers and enrolled by convenient sampling technique. A questionnaire was used to collect socio demographic and clinical data through face to face interview. Capillary blood samples were collected and used to prepare thin and thick blood smears, which were then stained using 10% Giemsa and examined under light microscope. Logistic regression was used to assess factors associated with malaria. Adjusted odds ratio with 95% confidence interval was calculated and P-value < 0.05 was considered statistically significant. Results The prevalence of malaria among symptomatic pregnant women was 20.8% (65/312) of which 12.2% (38/312), 4.8% (15/312) and 3.8% (12/312) were P. falciparum, P. vivax and mixed infections, respectively. Being illiterate (p< 0.001), first trimester (p = 0.036), primigravidae (p<0.001), living far from health center (p<0.001), not sleeping under long lasting insecticide treated nets (p<0.001) and living near irrigation areas (p = 0.006) were significantly associated with prevalence of malaria in malaria symptomatic pregnant women. Conclusions Even though prevalence of malaria is decreasing in the country because of scale-up of intervention and prevention measures, this study showed that, malaria is still the major public health problem among pregnant women. Being illiterate, first trimester, primigravidae, living far from health centers, not sleeping under long lasting insecticide treated nets and living near irrigation areas were factors that increased the prevalence of malaria in malaria symptomatic pregnant women. Therefore, special attention should be given to pregnant women prone to these factors.